2017
DOI: 10.1002/hbm.23903
|View full text |Cite
|
Sign up to set email alerts
|

Relations between cortical thickness, serotonin 1A receptor binding, and structural connectivity: A multimodal imaging study

Abstract: Serotonin 1A (5-HT ) receptors play a direct role in neuronal development, cell proliferation, and dendritic branching. We hypothesized that variability in 5-HT binding can affect cortical thickness, and may account for a subtype of major depressive disorder (MDD) in which both are altered. To evaluate this, we measured cortical thickness from structural magnetic resonance imaging (MRI) and 5-HT binding by positron emission tomography (PET) in an exploratory study. To examine a range of 5-HT binding and cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…We posit that the associations between early-treatment rACC cortical thickening and sertraline treatment response may be a marker for a normative SSRI mechanism of action, whereby increased 5-HT 1A receptor concentrations occur cortically in the acute phase of treatment. This hypothesis is bolstered by recent evidence suggesting a positive relationship between CT and 5-HT 1A receptor concentration in a range of cortical regions [56]. Although speculative and unable to be tested within this study, the cortical thickness alterations may be a consequence of fluctuations in cortical 5-HT 1A receptor concentrations.…”
Section: Discussionmentioning
confidence: 54%
“…We posit that the associations between early-treatment rACC cortical thickening and sertraline treatment response may be a marker for a normative SSRI mechanism of action, whereby increased 5-HT 1A receptor concentrations occur cortically in the acute phase of treatment. This hypothesis is bolstered by recent evidence suggesting a positive relationship between CT and 5-HT 1A receptor concentration in a range of cortical regions [56]. Although speculative and unable to be tested within this study, the cortical thickness alterations may be a consequence of fluctuations in cortical 5-HT 1A receptor concentrations.…”
Section: Discussionmentioning
confidence: 54%
“…In major depression and mild cognitive impairment, deficits in gray matter volume and 5-HT innervation are seen in the PFC 82 , 83 , and reduced cortical thickness has been associated with 5-HT genetic markers 84 , 85 . The finding that effective treatment of major depression is associated with a reversal of reduced cortical thickness 86 and increased connectivity to the 5-HT system 87 , 88 suggests that SSRI-induced axonal neuroplasticity may be an important mechanism in its antidepressant actions in humans 8 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…122 Although the role of 5-HT 1A receptors in 5-HT neuronal development remains to be elucidated, there is evidence that hippocampal 5-HT 1A heteroreceptors signal to CREB to enhance developmental hippocampal synapse formation. 123,124 A similar developmental mechanism could be linked to the above-mentioned correlations between 5-HT 1A receptor levels and grey-matter thickness in certain brain regions, 92 which is altered in major depression. 125 In addition to influencing neurodevelopment, there is evidence that antidepressant-induced signalling through 5-HT 1A receptors can affect neuroplasticity in adulthood.…”
Section: Htr1a Genotype Neurodevelopment and Neuroplasticitymentioning
confidence: 92%
“…91 Other studies have shown that levels of raphe and cortical 5-HT 1A receptors detected using [ 11 C]WAY100635 binding are increased in depressed patients and correlate with cortical thickness and tract number in the posterior cingulate cortex, part of the DMN. 92 Conversely, in healthy people [ 11 C]WAY100635 binding was negatively correlated with posterior cingulate cortex and medial dorsal PFC activity. 93 These studies suggest that the 5-HT 1A receptor regulates the DMN, but in opposite ways in healthy people compared to people with depression.…”
Section: Htr1a Rs6295 and Phenotypic/brain Network Alterationsmentioning
confidence: 99%